Roadmap for Safer and Resilient Schools : Guidance Note 2 - World Bank (World Bank, Washington, DC, 2020)
The Roadmap for Safer and Resilient Schools (RSRS) is a step-by-step guide intended to provide support to governments of developing countries that are exposed to natural hazards. Specifically, it focuses on the design of intervention strategies and investment plans to make schools safer and resilient at scale. The guide also encompasses the recovery and reconstruction of school facilities affected by disasters. The RSRS aims to promote cooperation among stakeholders involvedin the planning, design, and implementation of risk reduction programs across large stocks of school facilities. Key stakeholders in this effort are school infrastructure managers, relevant government agencies, ministries of finance, the World Bank, and other international financinginstitutions (IFIs) and development partners. The RSRS stems from the experience of World Bank task teams working in this field.